No effect of fluid intake on neutrophil responses to prolonged cycling - Bishop, N. C.; Scanlon, G. A.; Walsh, N. P.; McCallum, L. J.; Walker, G. J. (Journal of Sports Sciences, 2004)
Ingesting carbohydrate beverages during prolonged exercise is associated with fewer numbers of circulating neutrophils and attenuated neutrophil functional responses, yet there is little information about the effect of fluid intake alone on immune responses to prolonged exercise. The aim of this study was to examine the influence of regular fluid ingestion compared with no fluid ingestion on plasma cortisol, circulating neutrophil and lipopolysaccharide (LPS)-stimulated neutrophil degranulation responses to prolonged cycling. In a randomized design, nine recreationally active males cycled for 2 h at 65% &Vdoti;O2max on two occasions with either fluid ingestion (lemon-flavoured water, fluid trial) before and during the exercise, or with no fluid intake at all (no fluid trial). Venous blood samples were obtained at rest, immediately after exercise and 1 h after exercise. Immediately after exercise, the plasma cortisol concentration was significantly higher in the no fluid trial than in the fluid trial (592?±?62 vs 670?±?63 nmol?·?l-1, P ?<?0.05). Circulating numbers of neutrophils increased 4.5-fold (P ?<?0.01) and LPS-stimulated elastase release per neutrophil decreased 34?±?7% (P ?<?0.01) immediately after exercise; there were no differences between trials. These results suggest that in ambient environmental conditions, fluid ingestion alone has a negligible effect on circulating neutrophil and LPS-stimulated neutrophil degranulation responses to prolonged exercise.